2022
DOI: 10.3389/fcimb.2022.882498
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Alkaline Phosphatase Prevents Sulfate Reducing Bacteria-Induced Increased Tight Junction Permeability by Inhibiting Snail Pathway

Abstract: Tight junctions (TJs) are essential components of intestinal barrier integrity and protect the epithelium against passive paracellular flux and microbial translocation. Dysfunctional TJ leads to leaky gut, a condition associated with diseases including inflammatory bowel disease (IBD). Sulfate-Reducing Bacteria (SRB) are minor residents of the gut. An increased number of Desulfovibrio, the most predominant SRB, is observed in IBD and other diseases associated with leaky gut. However, it is not known whether De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…20 Singh et al emphasizes the use of recIAP as a new therapeutic approach to address leaky gut caused by sulfate-reducing bacteria of snail. 21 Furthermore, supplemented recIAP significantly reduced gut barrier damage, decreased bacterial translocation to the systemic organs, and attenuated systemic inflammation. 22 Overall, bIAP is inexpensive and well-suited for animal or cellular experiments, while the high purity and safety of recIAP have made it more widely used in clinical studies.…”
Section: Iap and Its Involvement In Signal Transductionmentioning
confidence: 93%
See 1 more Smart Citation
“…20 Singh et al emphasizes the use of recIAP as a new therapeutic approach to address leaky gut caused by sulfate-reducing bacteria of snail. 21 Furthermore, supplemented recIAP significantly reduced gut barrier damage, decreased bacterial translocation to the systemic organs, and attenuated systemic inflammation. 22 Overall, bIAP is inexpensive and well-suited for animal or cellular experiments, while the high purity and safety of recIAP have made it more widely used in clinical studies.…”
Section: Iap and Its Involvement In Signal Transductionmentioning
confidence: 93%
“…Recent work has shown the importance of recIAP in maintaining gut integrity . Singh et al emphasizes the use of recIAP as a new therapeutic approach to address leaky gut caused by sulfate-reducing bacteria of snail . Furthermore, supplemented recIAP significantly reduced gut barrier damage, decreased bacterial translocation to the systemic organs, and attenuated systemic inflammation .…”
Section: Iap and Its Involvement In Signal Transductionmentioning
confidence: 99%
“…Recent work has demonstrated that Desulfovibrio spp. induced intestinal permeability via the snail pathway [126]. Snail is a transcription factor associated with increased intestinal permeability [127][128][129] via negatively regulating tight junctions [130,131].…”
Section: Increased Intestinal Permeabilitymentioning
confidence: 99%
“…Factors resulting from dysbiosis, such as increases in LPS [ 99 101 ] and Desulfovibrio spp. [ 126 ] also lead to leaky gut. Recent work has demonstrated that Desulfovibrio spp.…”
Section: Consequences Of Dysbiosismentioning
confidence: 99%
“…The intestinal mucus layer, an essential component of the intestinal barrier, ensures host immune homeostasis by isolating the immune system from gut microbiota. , Some pathogenic bacteria (e.g., Escherichia coli and Desulfovibrio ) have been reported to reduce mucins and tight junction proteins in the intestine, resulting in increased intestinal permeability. The liver is an important target organ of insulin that plays a dominant role in glucose homeostasis . Notably, the intestines and liver are closely linked by the biliary tract, portal veins, and circulation.…”
mentioning
confidence: 99%